The Effect of Pilocarpine Hydrochloride on The Occurrence of Temporal Lobe Epileptic Seizures in White Mice (Mus musculus L.) BALB/C Strain - Audria, Intan Safira; Harkitasari, Saktivi; Diah Witari, Ni Putu; Ningrum, Rima Kusuma; Putra Parwati, Tjok Istri; Sumadewi, Komang Trisna; Wiranatha, I Gede; Pratiwi, Cokorda Agung (Biology, Medicine, & Natural Product Chemistry, 2025)
The objective of this research was to determine the effective dosage of pilocarpine hydrochloride to provoke epileptic seizures in animal models. In this study, a true-experimental method was utilized, employing a post-test only control group design. A total of 32 white mice (Mus musculus Linnaeus UICC 524) BALB/c strains were divided into four different groups for this study. The experimental groups were subjected to varying dosages of pilocarpine hydrochloride: 220 mg/kgBW as group I, 320 mg/kgBW as group II, and 350 mg/kgBW as group III. On the other hand, the control group was administered a saline solution (NaCl 0.9%) at a dosage of 0.16% ml/kgBW. Both pilocarpine hydrochloride and saline solution (NaCl 0.9%) were injected intraperitoneally (i.p) into mice. In group I, none of the mice experienced epileptic seizures, and they all survived. In contrast, in group III, all the mice experienced epileptic seizures, but none of them survived. The Man-Whitney Test showed significant differences in seizure occurrence across doses (p<0.01). The effective dose of pilocarpine hydrochloride for inducing epileptic seizures associated with temporal lobe epilepsy (TLE) in this study appears to be in the range of 320 mg/kgBW to 350 mg/kgBW.